Interleukin-6 via Toll-Like Receptor 3 Signaling Attenuates the Expression of Proinflammatory Chemokines in Human Podocytes - Hidenori Umetsu; Shojiro Watanabe; Tadaatsu Imaizumi; Tomomi Aizawa; Koji Tsugawa; Shogo Kawaguchi; Kazuhiko Seya; Tomoh Matsumiya; Hiroshi Tanaka (Karger Publishers, 2021)
Background: Although toll-like receptor 3 (TLR3) signaling is involved in the development of certain chronic kidney diseases, the specific molecular mechanisms underlying inflammatory reactions via activation of TLR3 signaling in human podocytes remain unclear. Interleukin (IL)-6 is a pleiotropic cytokine associated with innate and adaptive immune responses; however, little is known about the implication of IL-6 via the activation of regional TLR3 signaling in the inflammatory reactions in human podocytes. Methods: We treated immortalized human podocytes with polyinosinic-polycytidylic acid (poly IC), an authentic viral double-stranded RNA, and assessed the expression of IL-6, monocyte chemoattractant protein-1 (MCP-1), and C-C motif chemokine ligand 5 (CCL5) using quantitative real-time reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay. To further elucidate the poly IC-induced signaling pathway, we subjected the cells to RNA interference against IFN-β and IL-6. Results: We found that the activation of TLR3 induced expression of IL-6, MCP-1, CCL5, and IFN-β in human podocytes. RNA interference experiments revealed that IFN-β was involved in the poly IC-induced expression of IL-6, MCP-1, and CCL5. Interestingly, IL-6 knockdown markedly increased the poly IC-induced expression of MCP-1 and CCL5. Further, treatment of cells with IL-6 attenuated the expression of CCL5 and MCP-1 mRNA and proteins. Conclusion: IL-6 induced by TLR3 signaling negatively regulates the expression of representative TLR3 signaling-dependent proinflammatory chemokines in human podocytes.